2013
DOI: 10.1177/0306624x13494076
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Desistance From Substance Use Among Reentering Offenders

Abstract: Prior research has indicated an inverse relationship between religion and criminal behavior; however, few studies have specifically examined the effect of spirituality on the desistance process among a contemporary and diverse sample of reentering drug-involved offenders. A comprehensive understanding of how spirituality is related to desistance from substance use can lead to more effective and evidence-based preventive and rehabilitative interventions. Using data from a longitudinal study of 920 diverse offen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 52 publications
2
39
0
1
Order By: Relevance
“…Organized religion can provide an accessible “cognitive blueprint” for prosocial decision making and behavior for individuals who may lack appropriate role models and examples in their social environments (Giordano, Longmore, Schroeder, & Seffrin, 2008). Identification as a religious person may increase one’s social capital and respectability; religious teachings may offer a mechanism of external social control; a spiritual or religious community can serve as a prosocial network; and feelings of being forgiven and loved by God may provide emotional support and feelings of peace and happiness that reduce the stress that might otherwise manifest itself in violent behavior or drug abuse (Bakken, Gunter, & Visher, 2013; Giordano et al, 2008). Women may also have stronger desires to build and maintain spiritual relationships, just as they care more about personal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Organized religion can provide an accessible “cognitive blueprint” for prosocial decision making and behavior for individuals who may lack appropriate role models and examples in their social environments (Giordano, Longmore, Schroeder, & Seffrin, 2008). Identification as a religious person may increase one’s social capital and respectability; religious teachings may offer a mechanism of external social control; a spiritual or religious community can serve as a prosocial network; and feelings of being forgiven and loved by God may provide emotional support and feelings of peace and happiness that reduce the stress that might otherwise manifest itself in violent behavior or drug abuse (Bakken, Gunter, & Visher, 2013; Giordano et al, 2008). Women may also have stronger desires to build and maintain spiritual relationships, just as they care more about personal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly relevant to criminologists is the evidence that suggests that meditative practices have the potential to address psychosocial processes that are clearly related to recidivism. For example, research has highlighted that some practices have been found to be helpful in the control of anger that can often lead to violence, and in the reduction of substance dependency (Bakken et al, 2014; Howells et al, 2010). This has important implications, given the evidence that suggests that both drug addiction and violence are often carefully intertwined with gang membership (Densley, 2013; Deuchar, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The qualitative studies on posttraumatic growth among offenders also highlighted the importance of religious or spiritual coping. In the general literature on coping with imprisonment, spirituality and religion have been described as a key resource for many prisoners (e.g., Allen, Phillips, Roff, Cavanaugh, & Day, 2008;Bakken, DeCamp, & Visher, 2014;Eytan, 2011;Mandhouj, Aubin, Amirouche, Perroud, & Huguelet, 2014;Schneider & Felty, 2009;Tehrani, 1997). O'Connor and Duncan (2011) argued that prisoners attend religious, spiritual, and humanistic practices much more than they did before they got incarcerated.…”
Section: Posttraumatic Growth and The Role Of Coping Strategiesmentioning
confidence: 99%